Proposta e implantação de uma sistemática de CCQ em uma empresa de pequeno porte - Garlet, Eliane (2015)
The use of methodologies such as Quality Control Circle (QCC) involving group activities to identify and solve problems in the workplace results in the improvement of this site and in employee motivation. Thus the employee has the opportunity to make suggestions to improve and to be more involved with the company. This research aims to propose and implement a system of QCC in a small business located in the central region of Rio Grande do Sul. This research is characterized as an action research with qualitative approach of exploratory, descriptive and explanatory character. From the main results obtained, we highlight the importance of this work to the area of Production Engineering before the activities developed, where it was shown that the QCC can be deployed in a small business. It is important to point that a proposal for a systematic of QCC was created and deployed; a training was provided to employees on the methodology and quality tools; projects were developed within established goals for quality, productivity and safety; development of a simplified QCC manual. In addition, the research provided a cultural change within the company, increasing the motivation of QCC members in becoming more involved. The environment of the company became cleaner and more organized with the implemented projects. Finally, we highlight the importance of research for small and medium businesses.